PERENCANAAN GELAGAR BETON PRATEGANG PADA JEMBATAN KEUDE RANTO PEUREULAK KABUPATEN ACEH TIMUR - Wahyuni Wahyuni; Herri Mahyar (Politeknik Negeri Lhokseumawe, 2017)
Keude Ranto Peureulak Bridge a bridge connecting Keude Ranto Panjang with Keude Geurobak village and other villages in Ranto Peureulak Sub-district, East Aceh District. Keude Ranto Peureulak Bridge is planned with a span length of 20.8 meters and width of 7 meters. The longitudinal axis planned for the bridge is the posttractive pretreat type concrete girder. The girder plan includes gelagar dimensioning, stress calculation, prestress loss, cross-sectional capacity, deflection control, and drawing. The quality of concrete used is fc = 40 Mpa, the tendon used is seven wire strand diameter ½ inch with 51 mm diameter tendon sheath. Tendon fpu voltage = 1860 Mpa, fy threaded steel reinforcement = 320 Mpa, plain steel reinforcement fy = 240 Mpa, and efficient cross-sectional height is 0.9 meters. From the calculation results obtained the moment that occurred on the girder of 2563,439 kNm on the calculation of the third combination. The number of tendons obtained from the calculation is 3 pieces with 7 pieces of strand on each tendon. Losing the total prestress force is 380,694 Mpa. The principal reference is used D13 mm, the shear reinforcement is used Ø10-100 mm at the support area and Ø10-600 mm in the field area. The ultimate moment capacity of the prestress beam is 5575.60 kNm from the calculation of the third combination. The largest deflection of 0.0247 meters due to a combination of two loads. All the results of the calculations obtained are safe to use.Keywords: girder, prestress, tendon, reinforcement, deflection